INDEKS KETERBACAAN TEKS BAHASA INGGRIS - Liliek Soepriatmadji (Dinamika Bahasa dan Budaya, 2013)
This study isaimed at construing: (1) the readability of English texts presented in SMA andMA state test paper 2011-2012; (2) the related variables. The data of thisstudy are all the English texts found in the test paper and are analyzed usingWhite Smoke Writer. The results are as follows: (1) the readability index is8.01. This may mean that the texts are moderately easy; (2) the variables coversentence count, word count, average sentence length; style (passive verb,negative sentence, informal expression, complex word, repetition, punctuation);grammar (tense, article, preposition,apostrophe, plural, conjunction, sentence completeness); spelling andsuggestion. Pedagogically, the study reminds readers of the importanceof analyzing text readability prior to using it in a test paper and in areading class. In addition, the software can be fascinatingly used to helplearners to edit their short functional texts, paragraphs, and texts.   KEY WORDS: readability, text, grammar, national test.